TAX E-FILING AND TAX COMPLIANCE IN TEN YEARS: A BIBLIOGRAPHY APPROACH - Diana Airawaty; Wahyu Widarjo (Universitas Mercu Buana Yogyakarta, 2021)
This study aims to review the researches on electronic tax filing which have affects to Tax Compliance in accredited scientific journal for 10-year period. The review was conducted against 99 articles relating to e-filing and tax compliance in various countries. The observation period started from 2010 – 2019. This examination used